2000
DOI: 10.1002/1097-0231(20000815)14:15<1345::aid-rcm22>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Carbon assimilation and turnover in grassland vegetation using anin situ13CO2 pulse labelling system

Abstract: A mobile laboratory was developed to administer a controlled flow of 13C labelled CO2 at ambient concentrations (∼350 ppm) in the field. The stable isotope delivery (SID) system consists of an isotope‐mixing unit with flow control to a series of 12 independent labelling chambers. In‐line CPU controlled infrared gas analysers allow automated measurement of chamber CO2 concentrations and gas flow management. A preliminary experiment was established on an upland pasture located at the NERC Soil Biodiversity exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(67 citation statements)
references
References 16 publications
9
57
1
Order By: Relevance
“…A lower proportion of recovered 13 C (10 %) is lost from shoots by shoot respiration and belowground transport in the fenced plots than that in the grazed plots (16 %) during the first 24 h after labeling. These estimations in the two treatments were much lower than the value of 36.7 % reported by Wu et al (2010) and 77 % found by Ostel et al (2000).…”
Section: Effect Of Exclosure On 13 C Dynamic and Allocationcontrasting
confidence: 74%
“…A lower proportion of recovered 13 C (10 %) is lost from shoots by shoot respiration and belowground transport in the fenced plots than that in the grazed plots (16 %) during the first 24 h after labeling. These estimations in the two treatments were much lower than the value of 36.7 % reported by Wu et al (2010) and 77 % found by Ostel et al (2000).…”
Section: Effect Of Exclosure On 13 C Dynamic and Allocationcontrasting
confidence: 74%
“…It may therefore be likely that changes occurring in these operationally defined active communities may be more relevant in terms of ecosystem functioning. Further, technologies which directly link the activity of microbes with ecosystem processes, such as the labeling of plant material with 13 CO 2 (37) and phylogenetic analysis of isotopically enriched rRNA (30), may be a more appropriate way of subdividing the community for more-resolved analyses of the response to perturbation.…”
Section: Discussionmentioning
confidence: 99%
“…DNA and RNA enable description of the total and active community, respectively (Ostle et al 2000;Kreuzer-Martin 2007). The involvement in the decomposition process can only be traced with highly labeled substrates using stable isotope probing (Kreuzer-Martin 2007).…”
Section: Role Of Soil Microorganismsmentioning
confidence: 99%